Conversational artificial intelligence (AI) and bank operational efficiency - Gumbo, Lilian; Mashizha, Margaret; Simon, Chosani; Phiri, Phillipa (International Journal of Accounting and Management Information Systems, 2023)
Purpose: The main objective of the research was to analyse the effects of conversational artificial intelligence (AI) on bank operational efficiency. The emergency of conversational artificial intelligence (AI) has revolutionised the way business interacts with its customers. Research methodology: The study employed a mixed- method approach where interviews and questionnaires were used to collect qualitative and quantitative data. A sample of 92 bank employees was drawn from ten Zimbabwean banks. Results: Conversational AI has a positive impact on banking operational efficiency. Specifically, conversational AI improves customer services by providing faster and more accurate responses to customer inquiries, reduces operational costs by automating routine tasks and improve workflow efficiency. Conclusion: Conversational AI significantly improves banking operational efficiency by automating routine tasks, enhancing customer service, and reducing costs. It streamlines processes and delivers accurate, real-time responses, reinforcing the value of its integration in banking operations. Broader research across regions and sectors is suggested to validate these findings further. Limitations: The study concentrated on the banking industry of one particular country. Contribution: The study makes a significant contribution in understanding the advantages of adopting conversational artificial intelligence in banking operations.